Pleural infection: moving from treatment to prevention - Bedawi, EO; Rahman, NM (European Respiratory Society, 2020)
The incidence of pleural infection is rising, and most clearly in the elderly, where it is associated with the highest mortality. Despite notable limitations in animal models replicating the human pleural space, there has been some progress in our understanding of the evolution of pleural infection. Studies continue to demonstrate that the microbiology is inherently different from pneumonia, emphasising that this is a distinct disease. Great headway has been made in the last decade with regard to optimising drainage. The place of intrapleural enzyme therapy in the therapeutic armamentarium is growing in importance, with research efforts now focused on optimising dosing, administration and exploring new targets. Surgery continues to play an important role, but timing and patient selection remain unclear. An increased awareness of at-risk groups coupled with early aggressive management strategies supported by risk stratification at the time of presentation are likely to be essential components in aiding the healthcare community to improve outcomes of this morbid condition.